La disciplina áulica en el rendimiento escolar de los niños /as del iv año básica del centro de educación básica Laura Carbo Núñez del cantón Ventanas, provincia de los Rios, del periodo 2011-2012. - Loor Zambrano, Celenita Jacinta (2012)
The present investigative work in his first part is dedicated exclusively upon presentment of the subject, in whose antecedents a brief synthesis of the education at world-wide level is made, national and regional. In the justification it is made notice the main aspects that make the investigation viable, taking in consideration the necessity that reorients the process of learning by means of the adoption of didactic activities that help the improvement of the discipline and will serve like support in its scholastic yield. The report consists of a general mission the same one that the global solution of the problem looks for and of three specific objectives that sustain to the general mission and the chapters of the document. In sequential form it is pointed out the hypothesis and one has settled down the variables that have been properly operacionalizadas. In the Theoretical chapter I Marco, in agreement with thematic and the problem it is pointed out the Scientific Theory that it is a summary of the improvement of the discipline, for the scholastic yield of the children and children. Chapter II, corresponds to the Methodological Strategies that have been put in practice for the accomplishment of this work, has been used several types of investigation as well as general and Particular methods, with regard to the population work yet universal since it is a manageable population. In chapter III, one makes reference, analysis upon presentment and interpretation of results of the investigation, such that after being tabs and porcentualizados, appears them in its respective picture, whose data give like result the respective graph that gives a visual idea us of the investigated aspect and simultaneously allow to establish a conclusion; concluding the chapter with the recommendations. Chapter IV is dedicated completely to the proposal, the same one that it has as title “TO DISCIPLINE PLAYING” to discipline playing one oportunided to improve the student coexistence. . This proposal persecutes to animate to the teachers and flexible teachers to be opened and, to take into account the opinion of its students, to make use of activities of coexistence that affect to the improvement of the discipline in the classroom, and thus form human beings complete, able to face the challenges that appear to him within the modern society.